The concentration of tumor necrosis factor alpha in periapical lesions - Popović Jelena; Cvetković Tatjana; Džopalić Tanja; Mitić Aleksandar; Nikolić Marija; Barac Radomir; Živković Slavoljub (Serbian Medical Society - Dental Section, Belgrade, 2014)
Introduction. The balance between proinflammatory and anti-inflammatory cytokines plays an important role in the pathogenesis of chronic periapical lesions. The aim of this study was to determine the concentration of TNF-α in tissue homogenates of periapical lesions and analyze its levels in relation to the symptomatology and the size of lesions. Materials and Methods. 93 samples of chronic periapical lesions were obtained after extraction of teeth. Samples were classified according to the clinical presentation as symptomatic and asymptomatic, and according to the size as large and small. The concentration of TNF-α was analyzed using ELISA. Results. The results showed increased production of TNF-α in symptomatic lesions compared to asymptomatic. Higher concentration of TNF-α was demonstrated in large lesions compared to small. Large symptomatic lesions showed greater concentration of TNF-α compared to small symptomatic lesions, while bigger asymptomatic lesions demonstrated higher amount of the cytokines compared to small asymptomatic lesions. Conclusion. Higher concentration of TNF-α in large symptomatic lesions indicates that TNF-α is an important factor responsible for the progression of lesions.